2014
DOI: 10.1002/ardp.201300287
|View full text |Cite
|
Sign up to set email alerts
|

A Review (Research and Patents) on Jasmonic Acid and Its Derivatives

Abstract: In medicinal chemistry there is a growing interest in using small molecules, including plant stress hormones. Jasmonic acid (JA) and its volatile methyl ester (MJ), collectively termed jasmonates, are lipid‐derived cyclopentanone compounds that occur ubiquitously and exclusively in the plant kingdom. This review covers the synthesis, usage, and biological activities of JA and its derivatives. A brief overview of the available information on JA and its features is given, followed by a detailed review of JA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 102 publications
1
39
0
6
Order By: Relevance
“…Despite the enormous progress made in the field of JA, many aspects still remain to be elucidated. For instance, plants contain many types of JA precursors and JA metabolites [7,11,26], but it is not clear how these diverse JAs and bioactive analogs regulate multitude of plant development. Furthermore, whether some JA metabolic proteins such as Jasmonate O-methyltransferase, LOX2 and AOS, are expanded for environmental adaption remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the enormous progress made in the field of JA, many aspects still remain to be elucidated. For instance, plants contain many types of JA precursors and JA metabolites [7,11,26], but it is not clear how these diverse JAs and bioactive analogs regulate multitude of plant development. Furthermore, whether some JA metabolic proteins such as Jasmonate O-methyltransferase, LOX2 and AOS, are expanded for environmental adaption remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The conserved and diversified JA biosynthesis and signalling pathways in plant reproduction are highlighted, particularly in the regulatory link with the ABCE-genes during flower development. Table 1) [7,11,[25][26][27]. kat2 kat5 double mutants display shorter inflorescences that contain atypical internode spacing and changed anatomy as well as ectopic floral organs [27], mimicking phenotypes of the abnormal inflorescence meristem1 (aim1/Atmfp2) mutants [28].…”
Section: Introductionmentioning
confidence: 99%
“…Jasmonic acid (JA) and its derivatives are stress signalling molecules involved in plant defence and regulate various metabolic pathways along with other plant hormones (Ramakrishna & Ravishankar 2011;Pirbalouti et al 2014). The influence of JA and ASA on biomass and daidzin production using hairy root cultures of P. corylifolia was investigated in this study which revealed variable responses.…”
Section: Influence Of Chemical Elicitors On Biomass and Enhanced Daidmentioning
confidence: 99%
“…Numerous studies have shown that ABA is able to promote ethylene production in many fruits, such as mango [38], strawberry [39] and tomato [40], implying that ABA may function as an upstream regulator of ethylene biosynthesis and responses [41]. JAs, such as methyl jasmonate (MeJA), JA, and other derivatives, make the plant responsive to various biotic and abiotic stresses and are involved in fruit ripening [42,43,44,45]. Jia et al [46] found that exogenous MeJA mainly regulates the grapefruit ripening process through regulation of fruit colouring, softening, and aroma spreading.…”
Section: Introductionmentioning
confidence: 99%